Revamping the ever-changing landscape of drug development processes in the midst of COVID-19 pandemic. Issue 6 (June 2021) - Oo, Charles; Ameer, Barbara
Highlights: COVID-19 has revealed many shortcomings in drug development processes and accelerated innovation, despite inflicting human suffering and death tolls. The advent of antiviral therapeutics and COVID-19 vaccines yield hopes, while it is possible that pockets of virulence can remain. Actionable processes to be adopted for this crisis include regulatory partnership and leadership, good science, patient centricity, complex innovative design, global perspective, and team effort. We are poised to revamp the traditional drug development processes for the better, which will benefit humankinds after this health crisis. Abstract: Oncology is the frontline of drug development. The current pharmaceutical pipeline is disproportional focused on oncology, where about 1/3 of all phases of development is in this therapeutic area. The emphasis brings about substantial breakthroughs and has made positive impact on the quality of life. However, oncology remains a threat to human existence. To facilitate this process, a comprehensive list of novel/first molecularly targeted oncology drug approvals by the FDA from 2017 to 2020 is assessed. Here, we focus on molecularly targeted oncology drugs and not cytotoxic ones, although the latter remain important. To achieve this purpose, besides their sponsors, years of approval, drug classes, and cancer indications, clinical significance is included. The results show that approved molecularly targeted drugs span across diverse classes, including small molecule receptor inhibitors, and biologics such as monoclonal antibodies, antibody-drug conjugates, check-point inhibitors (i.e., PD1, PDL1, CTLA4) and CAR-T cell therapies. Although complete cure of cancer remains limited, we have made substantial inroads and more is yet to come. Moreover, many of these new knowledge can be extrapolated to other therapeutic areas, especially to those of currently unmet medical needs such as in neurology and other chronic diseases.